Socio-Biological Risk Factors for ADHD - Shevchenko, I (KnE Life Sciences, 2018)
The aim of this article was to show the relationships of socio-biological factors in the development of the child with ADHD with the degree of severity of the defect. As we tend to assume, both social and biological factors (together or separately) are not selective for the development of certain cognitive functions (for example, the early debut of the disease for the non-formation of control functions or pregnancy complications for the non-formation of auditory memory), and globally, in aggregate, influence the mental development of the child. The study allowed us to establish risk factors in which we can talk about the possibility of developing and aggravating ADHD, identify opportunities for its prevention and confirm the importance of early complex neuropsychological remediation in the treatment of the disease. Keywords: ADHD, socio-biological characteristics of the development, ADHD risk factors.